PENERAPAN SANKSI ADAT DALAM PENYELESAIAN TINDAK PIDANA PERJUDIAN DI KABUPATEN PESISIR SELATAN (STUDI KASUS PADA SATRESKRIM POLRES PESISIR SELATAN) - Muhardi, Muhardi (UNES Law Review, 2020)
The practice of gambling is growing day by day in various levels of society, from the lower classes to the upper classes. This was proven when the Pesisir Selatan Criminal Investigation Unit (Sat Reskrim) arrested 7 (seven) mothers who played playing card gambling in Kampung Samudera, Kenagarian Surantih, Sutera District, Pesisir Selatan on October 21, 2017. But before taking the route criminal law in general, this case has been resolved by customary law in Pesisir Selatan by receiving customary sanctions. This research is a descriptive analytical study. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. From the results of the research it can be explained that: First, the application of customary sanctions in the settlement of gambling crimes in Pesisir Selatan Regency, is by considering local rules and discretion made by the Head of Criminal Investigation Unit of the Pesisir Selatan Police. Where deliberation leaders, traditional, religious and family leaders hold a meeting, the results of the deliberation are conveyed to the police so that the suspects will be given customary sanctions, in the form of requiring them to walk from the location of arrest to one of the mosques, and vowing not to repeat the act again. Second, the obstacles to the application of customary sanctions in solving gambling crimes in Pesisir Selatan Regency are internal obstacles to the police and external obstacles to the police. There are settlement steps that can be taken in overcoming the obstacles that occur in overcoming gambling with preventive and repressive measures.